Quality of Service of Sub-Puskesmas in Bongohulawa Village, Limboto District, Gorontalo Regency - Kalsum Biga; Rusly Abdurrahman Idji (Borong Newinera Publisher, 2022)
This study aims to determine the service quality of the sub-health center (Health Center) in Bongohulawa Village. The research method uses a qualitative type. The results showed that the service of the sub-health center (Health Center) in the Bongohulawa Village, was not of high quality. Of the five indicators used as instruments, it shows that only one indicator is considered to have been fulfilled, namely the reliability indicator where Health Center Bongohulawa officers have knowledge and educational backgrounds that are in accordance with their field of work. The other four indicators are considered unfulfilled, namely physical evidence (tangibles), responsiveness (responsiveness), assurance (assurance), and empathy (empathy). This can be seen from the condition of facilities and infrastructure as well as the inadequate number of medical personnel, the low responsiveness of officers to the needs of the community in the health sector, the low public trust in the implementation of health services carried out by the Health Center and the low awareness of the Health Center which only provides health services for a month.